A 4-year study of the use of the short metacarpal cast in the management of metacarpal shaft fractures. (November 2021) - Street, Julia; Nessa, Luthfun; Logan, Andrew; Trickett, Ryan W
We report on our experience of using a short, moulded metacarpal cast over a 4-year period in the non-surgical management of metacarpal shaft fractures. Between 6 April 2015 and 6 April 2019, 117 patients were treated using this method. The majority were male, and the mean age was 24.6 years. The most common mechanism of injury was a punch injury (73 patients, 62%). Fifteen patients (13%) were treated for multiple metacarpal fractures. Immediately after cast removal, 68% had a full range of finger movement and 68% were pain free. Few required formal hand therapy. Fifteen patients experienced minor complications, primarily soft tissue irritation from the cast and non-limiting extensor lag. The moulded short metacarpal cast is an effective non-surgical treatment for angulated extra-articular metacarpal fractures of the diaphysis and diametaphyseal junction. Level of evidence: IV